Three generations. Oral testimonies on crime and social change in London's East End - Hood, Roger (The British journal of criminology, 1999)
This article compares, through the use of oral testimonies, the experiences of crime and social change of three generations of East Enders. Those aged 75 and older spoke about the period before the second world war; those in their mid fifties to early sixties about their experiences in the 1950s and early 1960s; those aged between 25 and 35 testified about the period between the late 1970s and the early 1990s. Each generation was asked not only about their experiences of victimization and/or involvement in committing offences, but also about the factors and relationships that acted as controls on crime. The testimonies suggest that different experiences of, and attitudes towards, crime of the different generations is related to the changing contexts of family life, community ties, leisure, economic prospects, social and cultural expectations and peer relationships